Gambaran Pengobatan Pasien Terkonfirmasi Covid-19 yang Melakukan Isolasi Mandiri di Rumah - Reni Ariastuti; Atik Aryani; Rita Septiana (Universitas Batanghari Jambi, 2022)
Covid-19 (Coronavirus Disease -19) pandemic is still a health problem for Indonesia and even the world. The limitations of health facilities such as hospitals in treating Covid-19 patients require Covid-19 patients with mild to moderate symptoms to self-quarantine/isolate at home. This study was conducted to see the description of treatment for confirmed Covid-19 patients who are self-isolating at home. The descriptive method was used in this study by purposive random sampling of confirmed Covid-19 patients who were self-isolating at home by filling out a questionnaire from a google form. The previous questionnaire had gone through the content validity stage by professional health workers, pharmacists, nurses and doctors. The data obtained were processed and analyzed in a qualitative descriptive manner based on the guidelines for the treatment of patients confirmed positive for COVID-19 from the Ministry of Health of the Republic of Indonesia and WHO (World Health Organization). This study displays data that there are 52 Covid-19 respondents who self-isolate at home, 75% receive doctor's prescription services and 25% without a doctor's prescription. The use of drugs on a doctor's prescription is in accordance with the Covid-19 therapeutic management from the Ministry of Health with the therapy given in the form of azithromycin, oseltamivir, vitamin C, vitamin D, and symptomatic therapy. While the use of drugs without a doctor's prescription, 8% use hard drugs without a doctor's prescription, while 92% of respondents use over-the-counter and limited-free drugs to treat symptoms and complaints. The treatment of Covid-19 patients who are self-isolating at home, whether with a doctor's prescription or not, is in accordance with the Covid-19 management guidelines from the Ministry of Health.